2013
DOI: 10.3109/09513590.2012.743009
|View full text |Cite
|
Sign up to set email alerts
|

Polycystic ovary syndrome and obesity do not affect vascular parameters related to early atherosclerosis in young women without glucose metabolism disturbances, arterial hypertension and severe abnormalities of lipid profile

Abstract: The aim of this study was to evaluate the influence of polycystic ovary syndrome (PCOS) and obesity on vascular parameters related to early atherosclerosis (VP-EA) [brachial flow-mediated dilation (FMD), carotid intima-media thickness (CIMT) and carotid arterial compliance (CAC)] in women with minor cardiovascular risk factors (CVRFs). Twenty-five young women with PCOS and 23 eumenorrheic women matched for body mass index (BMI) were studied. The women were subdivided according to BMI and PCOS status, and compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 25 publications
1
6
0
1
Order By: Relevance
“…However, our NW-NonPCOS and OB-NonPCOS group sample sizes are comparable with other pediatric (43) and adult (9, 10, 27, 50, 54) cross-sectional studies. Although selection bias of NW-NonPCOS and OB-NonPCOS could be contributory, there was no known family history of PCOS in our NW-NonPCOS subjects, and similar to the general US population, most of our OB-NonPCOS subjects had some family history of obesity, diabetes or CVD.…”
Section: Discussionsupporting
confidence: 74%
“…However, our NW-NonPCOS and OB-NonPCOS group sample sizes are comparable with other pediatric (43) and adult (9, 10, 27, 50, 54) cross-sectional studies. Although selection bias of NW-NonPCOS and OB-NonPCOS could be contributory, there was no known family history of PCOS in our NW-NonPCOS subjects, and similar to the general US population, most of our OB-NonPCOS subjects had some family history of obesity, diabetes or CVD.…”
Section: Discussionsupporting
confidence: 74%
“…42,44 As for the inflammatory molecules, data on the relationship between PCOS and carotid intima-media wall thickness (cIMT), a marker of preclinical atherosclerosis, are not conclusive. In a previous study, 25 in this same cohort of women, we have demonstrated that by adopting stricter diagnostic criteria and excluding major CV risk factors 25,45 no differences were evident in vascular parameters related to early atherosclerosis in women with PCOS. This was also shown by Kahal et al 46 by studying obese women with PCOS diagnosed by strict diagnostic criteria and matched not only for BMI but also for abdominal obesity, blood pressure, lipid profile and smoking history.…”
Section: Declaration Of Interestmentioning
confidence: 56%
“…The clinical and chemical characteristics of these groups have been previously described. 25 There was no difference between the medians of TNF-α among the four groups (p=0.296), while the medians of IL-6 levels were significantly higher in the ObeseControl group when compared with the Lean-Control group (p=0.009) and with the Lean-PCOS group (p=0.001). For hs-CRP, the median was higher in the Obese-Control and Obese-PCOS groups than in the Lean-Control group and in the Lean-PCOS group (Obese-Control vs Lean-Control, p=0.006 and Data are expressed as median (min-max); Mann-Whitney U test followed by Bonferroni adjustment was used to perform comparisons between PCOS and control groups, regardless of BMI, and between obese and lean groups, regardless of PCOS; p <0.005 was considered significant (p corrected); HOMA-IR: homeostatic model assessment of insulin resistance; AUCi: area under the curve of insulin during the oral glucose tolerance test; TNF-α: tumor necrosis factor-α; IL-6: interleukin-6; hs-CRP: high-sensitive C-reactive protein.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…The exact effect of PCOS on endothelial function remains controversial. Several studies have revealed that it is not impaired in women with PCOS who are either not obese or do not display morbid obesity [19,20]. However, some authors believe that endothelial function is impaired in patients with PCOS [3,21].…”
Section: Discussionmentioning
confidence: 99%